Crystal structure of zirconia affects osteoblast behavior. Issue 7 (July 2020) - Rohr, Nadja; Bergemann, Claudia; Nebe, J. Barbara; Fischer, Jens
Highlights: An increased surface roughness of zirconia reduces cell spreading of osteoblasts. An increased tetragonal phase ratio of zirconia increases cell viability of osteoblasts. Wettability is increased on zirconia after heat-treatment. Gene expression is comparable on smooth and micro-structured zirconia. Abstract: Objectives: Different approaches are currently undertaken to structure the endosseous part of zirconia implants. The purpose of the present study was to evaluate how surface roughness and monoclinic to tetragonal phase ratio of zirconia affect cell behavior of human osteoblasts. Methods: Zirconia discs with five different surface structures were produced: machined; machined heat-treated; polished; polished heat-treated; sandblasted, etched and heat-treated (cer.face 14, vitaclinical). The specimen surfaces were then characterized in terms of monoclinic to tetragonal phase ratio, wettability, roughness and visualized using scanning electron microscopy. To determine the reaction of the human osteoblastic cells (MG-63) to the surface roughness and monoclinic to tetragonal phase ratio of zirconia, cell spreading, morphology, actin cytoskeleton, viability and gene expression of alkaline phosphatase (ALP), collagen type I (COL) and osteocalcin (OCN) were assessed. Results: Heat-treatment of the specimens significantly improved the surface wettability. With increased surface roughness Ra of the specimens, cell spreading was reduced. Cell viability after 24 h correlated linearly with the tetragonal phase ratio of the specimens. Gene expression after 24 h and 3 d was comparable on all specimens irrespective their surface roughness or monoclinic to tetragonal phase ratio. Significance: Smooth zirconia surfaces with a high tetragonal phase ratio revealed best surface conditions for MG-63 osteoblastic cells and may be considered to design the endosseous part of zirconia implants.